1984
DOI: 10.21273/hortsci.19.5.676
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Genotype and Ethephon on Rhizoctonia Soil Rot of Processing Tomatoes

Abstract: Two Arkansas breeding lines, 2 USDA breeding lines, and 2 commercial cultivars were evaluated for resistance to fruit rot caused by Rhizoctonia solani Kuehn. Each line or cultivar was field evaluated for the percentage of rot of fruit touching the ground and for yield. Arkansas breeding lines and USDA breeding line 79B 888-3 had the lowest percentage of rot and the highest yield, whereas the commercial cultivars and USDA 79B 823-3 had the highest percentages of rot and the lowest yields. The use of Ethephon at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The results of the pathogenicity test (Table 2, Figure 6) revealed that all isolates of R. solani, Fusarium spp., and M. phaseolina caused a significant decrease in cucumber seed germination rate, ranging from 0-43.3% compared to the control, which exhibited 100% germination The findings indicated that isolates R7 to R15 of R. solani, 1F to F5 of Fusarium spp, and isolates M1 and M2 of significantly outperformed other isolates, which completely inhibiting seeds germination Meanwhile, the germination rate of the cucumber seeds treated with the isolates R1, R2, R3, R4, R5, and R6 ranged from 6.6 -43.3 %, respectively. Studies indicated [38][39][40], that the ability of these fungi to produce enzymes, toxins and toxic metabolites that manifest the symptoms above explain the reason for seed germination failure and seed rot Further findings by [41][42][43], indicate other forms of enzymes such as Cellulase, Pectinase, Protease, Amylase , etc facilitate fungi such as R. solani, Fusarium spp. and M. phaseolina to degrade host plant cell wall components to facilitating fungi penetrability into targeted tissues and exploit targeted cells' metabolic activities in the host There are studies of the other pathogen-produced phytotoxins such as Phenyl acetic acid and P or M -hydroxyl, produced by R. solani and Phaseolinone, Botryodiplodin, Phomenone and Gigantenone produced by M. phaseolina Fusarium spp.…”
Section: Effect Of Fungi Isolated From the Diseased Cucumber Plants O...mentioning
confidence: 99%
“…The results of the pathogenicity test (Table 2, Figure 6) revealed that all isolates of R. solani, Fusarium spp., and M. phaseolina caused a significant decrease in cucumber seed germination rate, ranging from 0-43.3% compared to the control, which exhibited 100% germination The findings indicated that isolates R7 to R15 of R. solani, 1F to F5 of Fusarium spp, and isolates M1 and M2 of significantly outperformed other isolates, which completely inhibiting seeds germination Meanwhile, the germination rate of the cucumber seeds treated with the isolates R1, R2, R3, R4, R5, and R6 ranged from 6.6 -43.3 %, respectively. Studies indicated [38][39][40], that the ability of these fungi to produce enzymes, toxins and toxic metabolites that manifest the symptoms above explain the reason for seed germination failure and seed rot Further findings by [41][42][43], indicate other forms of enzymes such as Cellulase, Pectinase, Protease, Amylase , etc facilitate fungi such as R. solani, Fusarium spp. and M. phaseolina to degrade host plant cell wall components to facilitating fungi penetrability into targeted tissues and exploit targeted cells' metabolic activities in the host There are studies of the other pathogen-produced phytotoxins such as Phenyl acetic acid and P or M -hydroxyl, produced by R. solani and Phaseolinone, Botryodiplodin, Phomenone and Gigantenone produced by M. phaseolina Fusarium spp.…”
Section: Effect Of Fungi Isolated From the Diseased Cucumber Plants O...mentioning
confidence: 99%
“…R. solani is one of the fastest pathogens that kill their hosts. It was found that degrading enzymes such as Pectinase, Pectin methylledterase, Cellulase, and Phosphatase are found to be associated with fungus, (Murphy et al, 1984;Dillard, 1987).…”
Section: Seed Germination and Pathogenicity Testsmentioning
confidence: 99%